Human Resources Perspectives: Intercultural Competence Benefits In Learning English and Japanese Languages Simultaneously - Girindra Putri Ardana Reswari; James Kalimanzila (Diponegoro University, 2021)
This research is aiming at discussing the benefits of learning English and Japanese languages simultaneously to cross-cultural competency. This article is also having a further discussion about the human resources development benefits gained from learning the two languages and cultures. English and Japanese are two languages that are famous as foreign languages for international business. It is because The United States, Japan, and the major economic forces of Western Europe are developed countries whose infrastructures and well-established financial markets are conducive to the operation and potential success of multinational corporations (MNCs). This study is a qualitative study with explanatory research as its method. The data gained by analyzing the perceptions drawn from the existing literature of various scholars documented in journals and books connected to Japanese and English languages, as well as human resources development issues. The results showed that learning Japanese and English simultaneously is also a good method in teaching the worker or students that will work in an international setting in having the comprehension of cross-cultural issues in general. The differences of those languages in terms of culture such as direct and indirect behavior in speaking, personal address system, and polite speech will become an example of understanding two different foreign language categories: high and low context cultures.